An investigation into the bacterial communities associated with pyrroloiminoquinone-producing South African latrunculid sponges - Hilliar, Storm Hannah (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Marine sponges belonging to the family Latrunculiidae are known for their production of cytotoxic pyrroloiminoquinone alkaloids and the South African coast provides a unique environment for the exploitation of these potent bioactive compounds. The isolation of structurally similar pyrroloiminoquinone compounds from unrelated, non poriferan sources has led to the suggestion that South African latrunculid pyrroloiminoquinones may be secondary metabolites produced by sponge associated microbial symbionts. Previous studies investigating the bacterial communities of South African latrunculid sponges have shown the conservation of distinct microbial populations with unusual bacterial taxa dominated by a novel betaproteobacterial and spirochete species. This study describes the further investigation into these associated bacterial communities, their conservation and sponge microbiome comparisons across spatial, temporal and environmental scales. The bacterial communities associated with seven latrunculid species representing three genera (Tsitsikamma, Cyclacanthia and Latrunculia) were characterized as well as a Mycale and Tethya rubra species. Latrunculid sponge microbiomes were significantly different from those associated with sympatric outlier sponge species and the surrounding environment. The bacterial communities associated with latrunculid sponges appear host specific with the conservation of two dominant bacterial symbionts which mirror the phylogeny of their host species.
Keywords: Sponges -- South Africa Algoa Bay; Betaproteobacteria; Spirochaeta; Symbiosis; Bacterial communities